Response of yearling steers to pasture burning, fertilization, and intensive early season stocking (bluestem pastures) - Berger, Loren Lynn; Harbers, L.H.; Schalles, R.R.; Smith, E.F.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2011)
Nine pastures totaling 492 acres were summer grazed by yearling Hereford steers. Five pastures were burned April 24, 1974; four were not burned. Burned and nonburned pastures had 0, 40, or 80 lbs. of nitrogen per acre applied aerially May 2, 1974. Stocking rates were determined with herbage production data from experimental plots under similar treatments. Under equal fertilization and stocking rates, burned pastures produced more average daily gain and gain per acre than nonburned pastures. Fertilizing and heavier stocking tended to reduce average daily gains, but increase gain per acre. Steers on the early-season, intensively grazed pasture, gained the most per day (2.09 lbs.) and produced a high gain per acre (96 lbs.). Range condition was higher on burned pastures. On unburned pastures, range condition decreased as fertilizer rate increased. High feed grain prices have forced beef producers to use forages to lower beef production costs. The native bluestem grasses have long provided a major portion of the forage for the Flint Hills beef producer and methods of increasing native grass production are being studied. Late spring burning (late April) has increased steer gains and improved range condition. Nitrogen fertilization has improved both the quantity and protein content of the forage produced, but also increased cool-season grasses and weedy species in the pastures. We are studying treatments explained above separately and in combination to evaluate effects they have on beef production and range condition. The effects of early-season, intensive stocking on a burned pasture also are being studied.
Keywords: Beef; Steers; Pasture burning; Fertilization; Stocking rate